Like Consort to Thyself Canst no Where Find: Gender Politics and the Rhetoric of Negation in John Milton’s Paradise Lost - Oliveros García, Jaime (Journal of Artistic Creation and Literary Research, 2025)
The social value of women during the Renaissance limited their intellectual interests to marriage and obedience to their partner. When a woman did not follow this pattern, she was considered a spinster. Women who showed intellectual inclinations in any way usually remained unmarried and part of a social group considered threating to society. In many cases they were accused of witchcraft and of being demon worshipers. This article deals with the Biblical figure of Eve, a woman created perfect, in similarity to the creator, but who does not follow the social norm, thus being the cause of what is known as the human Fall from divine Grace. In particular, I look at John Milton’s Paradise Lost where Eve stands as an allegorical figure that represents all women.